TITLE: THE COVID-19 MORATORIUM: A REPRIEVE AND NOT A WAIVER - Lohia, Palak (The journal of contemporary issues in business and government, 2021)
In the first MPC meeting held on 27.03.20, Finance Minister of India, Nirmala Sitharaman and the Governor of RBI, Shaktikanta Das announced a moratorium of three months on all loans and credit card instalments due between 1st March and 31st May initially, which was later extended to 31st August, in order to provide relief to the borrowers in the economy, in the current scenario of losses. Loans being on moratorium are sup- posed to have zero impact on the credit history of the borrower concerned, which means a no default situa- tion. Now, banking sector, which is the backbone of any economy, will have to carry the burden of this year for many more years to come. In this paper, it has been attempted to study the impact of the decision of putting the loans on moratorium on the banking industry of India, adding to the ever existing issue of high NPAs.